Early language and executive skills predict variations in number and arithmetic skills in children at family-risk of dyslexia and typically developing controls. (August 2015) - Moll, Kristina; Snowling, Margaret J.; Göbel, Silke M.; Hulme, Charles
Abstract: Two important foundations for learning are language and executive skills. Data from a longitudinal study tracking the development of 93 children at family-risk of dyslexia and 76 controls was used to investigate the influence of these skills on the development of arithmetic. A two-group longitudinal path model assessed the relationships between language and executive skills at 3–4 years, verbal number skills (counting and number knowledge) and phonological processing skills at 4–5 years, and written arithmetic in primary school. The same cognitive processes accounted for variability in arithmetic skills in both groups. Early language and executive skills predicted variations in preschool verbal number skills, which in turn, predicted arithmetic skills in school. In contrast, phonological awareness was not a predictor of later arithmetic skills. These results suggest that verbal and executive processes provide the foundation for verbal number skills, which in turn influence the development of formal arithmetic skills. Problems in early language development may explain the comorbidity between reading and mathematics disorder. Highlights: The same cognitive processes underlie arithmetic in at-risk and control children. Language and executive skills predict variation in preschool verbal number skills. Preschool number skills in turn predict arithmetic skills. Verbal number skills mediate the relation between early skills and arithmetic. Language problems may explain the comorbidity between reading and maths disorder.